Zircon coronas around Fe-Ti oxides: A physical reference frame for metamorphic and metasomatic reactions - Austrheim, H.; Putnis, Christine; Engvik, A.; Putnis, Andrew (Springer, 2008)
Ilmenite in coronitic gabbros from the Bamble and Kongsberg sectors, southern Norway, is surrounded by zircons ranging in diameters from a fraction of a micrometer to 10 µm across. The zircons are inert during subsequent metamorphism (amphibolite- to pumpellyite-prehnite facies) and metasomatism (scapolitization and albitization) and can be found as trails in silicates (phlogopite, talc, chlorite, amphibole, albite, and tourmaline) in the altered rocks. The trails link up to form polygons outlining the former oxide grain boundary. This 3-dimensional framework of zircons is used to (a) recognize metasomatic origin of rocks, (b) quantify the mobility of elements during mineral replacement, (c) establish the growth direction of reaction fronts and to identify the reaction mechanism as dissolution-reprecipitation. Zircon coronas on Fe-Ti oxides have been described from a number of terrains and appear to be common in mafic rocks (gabbros and granulites) providing a tool for a better understanding of metasomatic and metamorphic reactions. © Springer-Verlag 2008.